Investigating the Mechanical and Durability Properties of Geopolymer Concrete Based on Granulated Blast Furnace Slag as Green Concrete (Journal of Civil Engineering Researchers, 2023)
Geopolymer concretes (GPCs) are known as green, environmentally friendly, sustainable concretes in the development of the structural industry with superior mechanical performance and durability compared to ordinary Portland cement concrete (OPCC). This type of concrete emits less CO2 than OPCC and aims for efficient waste management while reducing environmental impacts. In this experimental research, 5 mixed designs were made of GPC based on granulated blast furnace slag (GBFS), which contains 0-8% Nano silica (NS) and 1-2% polyolefin fibers (POFs). A mixed design was also made of OPCC to compare with GPC. The tests of compressive strength, tensile strength, drop weight impact (DWI), Ultrasonic Pulse Velocity (UPV), water permeability and microstructural examination by scanning electron microscope (SEM) images and X-ray fluorescence (XRF) spectroscopy were performed on concrete samples and the results were analyzed and compared. The results obtained in this laboratory research, while overlapping with each other, indicate the superiority of mechanical properties and durability of GPC compared to OPCC.
Keywords: Geopolymer Concrete (GPC); Granulated Blast Furnace Slag (GBFS); Nano Silica (NS); Polyolefin Fibers (POFs); Mechanical and Durability Properties